The Influence of Promotion, Service Quality, and Customer Experience on Repurchase Intention in The Culinary Industry in Surabaya, Indonesia - Apreliana, Selvi; Hartini, Sri (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study examines the impact of promotion, service quality, and customer experience on repurchase intention in the culinary industry of Surabaya. Using a quantitative survey design, data were collected from 100 respondents who had visited Restaurant X at least twice in the past month. Validity and reliability tests confirmed the robustness of the measurement instrument (Cronbach's Alpha > 0.70). The findings indicate that service quality (β = 0.371, p = 0.002) and customer experience (β = 0.396, p = 0.000) significantly affect repurchase intention, while promotion (β = 0.123, p = 0.371) shows a positive but insignificant effect. The model explains 38% of the variance (R² = 0.380) in repurchase intention. These results highlight that restaurants should prioritize enhancing service quality and customer experience to foster loyalty rather than relying solely on promotions.